The effect of calcium fluoride on extracting magnesium from magnesite and calcium carbonate by silicothermal reduction in flowing argon - Guo J.-H.; Fu D.-X.; Han J.-B.; Ji Z.-H.; Wang Y.-S.; Zhang T.-A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
At present, the production of magnesium is mainly carried out semi-continuously with ferrosilicon as reducing agent under high temperature and high vacuum. In order to continuously produce magnesium, a new method of extracting magnesium from low-grade magnesite and calcium carbonate by silicothermal method in flowing inert gas was proposed. The effects of calcium fluoride (CaF2) on decomposition rate, decomposition kinetics, reduction rate of magnesia, and crystal type of dicalcium silicate in reduction slag were investigated in the paper. The experimental results showed that calcium fluoride could accelerate the decomposition of carbonate, and had no side effect on the calcined products. In addition, the analysis results of DTA curves showed that calcium fluoride could reduce the decomposition reaction activation energy and the reaction temperature of carbonate in the prefabricated pellets. The results of reduction experiments showed that proper calcium fluoride could promote the reduction rate of magnesia, and in the temperature range of 1250℃ ~ 1350℃, with the same timeframe, the corresponding calcium fluoride contents were 5%, 3%, and 1% respectively when the reduction rate reached the maximum. Excessive calcium fluoride reduced the reduction rate of magnesia, but it promoted the transformation of dicalcium silicate to γ phase in the reduction slag.